2004
DOI: 10.1007/bf02914517
|View full text |Cite
|
Sign up to set email alerts
|

One-stage Fowler-Stephens orchidopexy for impalpable undescended testis

Abstract: Our results for the one-stage FSO are comparable with other procedures for the management of high maldescended testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Evaluation of our results did show acceptable success rates (87.5%, 1 year) when compared with the results of other published studies [8,9]. Although in their original study, Dhannani et al [11] reported a meaningful success rate (98%) by performing a two stage FSO; we believe that our results with single stage procedure may be accepted as comparable with this study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Evaluation of our results did show acceptable success rates (87.5%, 1 year) when compared with the results of other published studies [8,9]. Although in their original study, Dhannani et al [11] reported a meaningful success rate (98%) by performing a two stage FSO; we believe that our results with single stage procedure may be accepted as comparable with this study.…”
Section: Discussionsupporting
confidence: 83%
“…Of these techniques, single stage FSO was performed by dividing the spermatic vessels well above the testis and carefully preserving the collateral vasal arteries by leaving a strip of peritoneum attached to the vas when dissecting it into the pelvis [7]. This technique was applied with varying success rates [7][8][9]. Docimo analyzed all the publications containing undescended testes and did not find out significant difference between the success rates of one or two stage FSO [10].…”
Section: Discussionmentioning
confidence: 99%
“…It involves division of the testicular vessels and relies on collateral deferential circulation. 6,15 Unfortunately, the dependence on collateral blood flow leaves the testes vulnerable to postoperative vasospasm or inadvertent injury to the vassal pedicle during dissection. However, this was felt to be more common when utilizing the open approach.…”
Section: Discussionmentioning
confidence: 99%
“…There have been cases utilizing alternative scrotal recipient vessels, including the deep circumflex iliac artery and pedal interpositional vein graft. 15 Earle et al also described the use of an omental pedicle flap in which the undescended testicle was marsupialized in a staged operation with the omentum. 17 The testicular autotransplantation procedure can be tedious and may take many hours of operative time.…”
Section: Discussionmentioning
confidence: 99%